2016
DOI: 10.4103/0019-5413.181788
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of arthroscopic subscapularis tendon repair: Are the results improving with improved techniques and equipment?

Abstract: Background:Rotator cuff tears are a common cause of shoulder pain and dysfunction. More recently, there has been a renewed interest in understanding the subscapularis tears. There are multiple articles in the literature showing the short term results of isolated subscapularis tendon repair. However, the midterm and long term outcome studies for arthroscopic subscapularis repair are few. This study evaluates the functional outcome after arthroscopic subscapularis repair.Materials and Methods:The records of 35 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(35 reference statements)
0
4
0
Order By: Relevance
“… 4 The incidence of subscapularis tears was shown to be between 3% and 13% by autopsy and cadaveric studies. 5 Subscapularis tears are hard to access, and they require advanced surgical techniques. 6 …”
mentioning
confidence: 99%
“… 4 The incidence of subscapularis tears was shown to be between 3% and 13% by autopsy and cadaveric studies. 5 Subscapularis tears are hard to access, and they require advanced surgical techniques. 6 …”
mentioning
confidence: 99%
“…Some studies reported the result of the subscapularis repair and attempted to correlate with tear classification. 1 , 3 , 6 , 35 Rhee et al used 2 different classification systems: Lafosse et al and Yoo et al. He found neither classification helpful in predicting the outcome of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous techniques published regarding arthroscopic treatment of subscapularis pathology; however, we believe that this technique is both simple and reproducible with excellent results, as reported by Katthagen et al and others. [9][10][11][12][13][14][15][16][17][18] Additionally, our stepwise approach with decompression of the subcoracoid space allows for safe manipulation of the subscapularis tendon in proximity to the neurovascular structures medially and inferiorly.…”
Section: Discussionmentioning
confidence: 99%
“…and others. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 Additionally, our stepwise approach with decompression of the subcoracoid space allows for safe manipulation of the subscapularis tendon in proximity to the neurovascular structures medially and inferiorly.…”
Section: Discussionmentioning
confidence: 99%